Cost-effectiveness of Intrathecal Baclofen Therapy in severe refractory non-focal disabling spasticity: a Spanish hospital perspective. (2nd January 2017) - Vidal, Joan; Slof, John; Serrano, David; Marqués, Teresa; Kumru, Hatice; Benito-Penalva, Jesús
ABSTRACT: Background : Current knowledge about long-term economic consequences of Intrathecal Baclofen Therapy (ITB Therapy®) is incomplete. Methods : A markov model was developed to estimate long-term clinical and economic outcomes with ITB Therapy® and conventional medical management of severe refractory non-focal disabling spasticity. Clinical and cost inputs were obtained through a non-interventional, prospective, observational study in a Spanish neurorehabilitation hospital. Results : ITB Therapy® increased remaining lifetime costs by €35, 605 and resulted in a gain of 1.06 quality-adjusted life-years (QALYs), thus showing an incremental cost-effectiveness ratio (ICER) of €33, 619/QALY gained. In alternative scenarios, reflecting other clinical settings and management options, considerably lower ICER values were obtained. In particular, opportunities were identified to improve efficiency by setting clinically and economically sound targets for post-operation length of stay. Conclusion : In the Spanish setting, ITB Therapy® resulted in an ICER close to €30, 000/QALY gained; potential ways to reduce costs and further enhance efficiency can be identified.